Gamified training: a new concept to improve individual soft skills - Ardian Adhiatma; Tina Rahayu; Olivia Fachrunnisa (Jurnal Siasat Bisnis, 2019)
This study discusses a new concept of "gamified training" through creative-oriented leadership. This concept aims to improve individual soft skills, such as communication skills, creative intelligence and collaboration skills. Gamified training is a design of training through gamification so that it will produce an effective and targeted training. Gamification is a training policy using game pattern. The sampling technique used purposive sampling method. The 106 respondents were involved in this study. Data collection technique used questionnaires and analyzed by regression method. The results showed that there was significant positive effect between creative-oriented leadership with gamified training. Furthermore, gamified training has also been proven to improve the individual soft skills.